Інтеграція захисних інструментів платіжних систем в механізм забезпечення безпеки банківської системи - Трусова, Наталя Вікторівна; Мельник, Олексій Васильович; Trusova, Natalia; Melnyk, Oleksii (Одеса : Видавничий дім «Гельветика», 2025)
UA: В статті розглянуто напрями інтеграції захисних інструментів платіжних систем в механізмі забез печення безпеки банківської системи на засадах регламентованих міжнародних стандартів оверсайту до ритмічності руху грошово-кредитних платежів, залучення капіталу в міжбанківській інфраструктурі, що імплементується в мережі метапростору через процес сек`юридизації та під дією FinTech-ресурсів попереджує загрозу в операційній діяльності банків, координує, пришвидшує їх взаємодію в FinTech середовищі. Обґрунтовано, що відсутність колаборації та адекватної стратегії співробітництва банків та FinTech-компаній щодо мінімізації ризиків платіжних систем в міжбанківській інфраструктурі призводить до послаблення політики безпеки банківської системи та деформації платіжного процесу в країні. Дове дено, що за наявності оцифрованих параметрів кіберзахисту платіжних систем змінюється дія механізму забезпечення безпеки банківської системи країни, який спрямований на попередження загроз в міжбан ківській інфраструктурі. /// EN: The article considers the directions of integration of protective instruments of payment systems in the mechanism of ensuring the security of the banking system on the basis of regulated international standards of oversight to the rhythm of the movement of monetary and credit payments, attracting capital in the interbank infrastructure, which is implemented in the metaspace network through the process of securitization and under the influence of FinTech resources prevents the threat in the operational activities of banks, coordinates, accelerates their interaction in the FinTech environment. It is substantiated that the lack of collaboration and adequate cooperation strategy of banks and FinTech companies to minimize the risks of payment systems in the interbank infrastructure leads to a weakening of the security policy of the banking system and deformation of the payment process in the bank network. An expanded categorical apparatus is proposed to interpret the essence of the mechanism of ensuring the security of the banking system and the risks of payment systems in a decentralized interbank infrastructure. It is proven that changes in the mechanism for ensuring the security of the country's banking system can have a relevant effect if there are digitized elements in the economic component of the mechanism, on which the processes of cyber protection of payment systems are based, aimed at preventing threats in banking customer service, achieving goals in operational activities, expanding opportunities in interbank infrastructure. Digitized elements in the economic component of the mechanism should form qualitative criteria for highly efficient and coordinated work of banks and FinTech companies. A clear regulation of the methodology for minimizing payment system risks by formative digital elements is determined, which take into account technological, spatial-protective, adaptive-protective, FinTech-analytical and FinTech-operational support for the totality of money and credit transfers made. The process of securitization of the payment portfolio of state-owned banks of Ukraine was assessed in order to ensure the security of the NBU's SEP.
Integration of payment system security instruments into the banking system security mechanis
Keywords: банківська система; платіжні системи; платіжні інструменти; FinTech-ресурси; ризики; загрози; кібезахист; міжбанківська інфраструктура; цифровізація; інтернаціоналізація; технології мета простору; banking system; payment systems; payment instruments; FinTech resources; risks; threats; cyber security; interbank infrastructure; digitalization; internationalization; metaspace technologies